Pulmonary metastases in pancreatic cancer, is there a survival influence? - Deeb, Ayham; Haque, Sulsal-Ul; Olowokure, Olugbenga (Journal of Gastrointestinal Oncology, 2015)
Pancreatic cancer is known to be one of the most lethal cancers. The majority of patients present with advanced stage disease, making curative approach unachievable. In untreated patients, the median survival does not exceed 6 months in metastatic disease and 10 months in locally advanced disease. Furthermore, the 5-year survival rate remains poor even in patients with early stage disease who are surgical candidates. The detrimental outcome is related to the high potency of developing metastasis which can be detected at diagnosis, when the disease progresses or relapses after surgery. Although the liver is the most common site of pancreatic cancer metastases, the cancer can escape the liver in some cases and metastasize to the lung or other distant organs. The involvement of some sites not others might reflect subgroups of this cancer with different molecular backgrounds. Identifying these groups may have utility in determining prognosis and stratifying treatment for patients.